Quando a fake vira news: uma análise das desinformações sobre vacina, do ponto de vista textual-discursivo - Ferreira, Marta Aparecida Paulo (2021)
To identify misinformation is not an easy assignment, considering they reaffirm political and ideological beliefs and positions, with technology as an ally they are shared by well-known people, which contributes to the real effect. This thesis, linked to the line of research Text and discourse in oral and written modalities, has as its theme the study of misinformation about vaccine, from a linguistic-discursive point of view. Thus, the general objective of this research is to contribute to the deepening of the study of fake news, with regard to its structural and linguistic aspects. Therefore, we list the following specific objectives: to present the concept of fake news, as well as other terms related to them and to mobilize concepts from different areas of the language sciences in order to verify their relationship with the process of constituting fake news; identify and describe and analyze the linguistic-discursive structures and strategies of fake news, evidencing its approximation with the news from the standard media. The research problem focuses on the following questions: To what extent are aspects of language sufficient to detect fake news? What linguistic-discursive strategies are used to build fake news so that it “feels” true? How are such strategies used for this purpose? In view of this, we start from two hypotheses: the first would be that the mode of organization and the linguisticdiscursive strategies used in the construction of fake news are close to the structure of the news genre and have the characteristics of traditional media; for this reason, they contribute to the spread and the reaffirmation of disinformation, giving it attributes of “truth”. The second hypothesis would be that the linguistic aspects, by themselves, are not effectively sufficient for the detection of fake news. The concept of disinformation adopted in this work is based on the postulates of Wardle (2017). Furthermore, to conceptualize the entire environment in which misinformation occurs, we started from the assumptions of Perosa (2017), Genesini (2018), Santaella (2018a, 2018b), Frias (2018), Ferrari (2018), Bucci (2018), Costa (2018). The theoretical foundation for Textual Linguistics is based on postulates based on studies by Fávero (1985a, 1985b, 2019); Ducrot (1987 [1084]); Van Dijk (1988); Alves Filho (2011); Fávero and Koch (2012 [1983], 2014 [1982]); Marcuschi (2002, 2014 [2008]); Costa Val (2004 [1991]); Bakthin (2011 [1992]); Antunes (2018) and Discourse Analysis, based on the postulates of Mussalim (2012); Charaudeau (2015). To compose the corpus of this research, we selected 14 misinformation about vaccine, more specifically those checked by the brazilian website named Health Without Fake News, from the Brazilian Ministry of Health. The results of the analysis show that the misinformation are not produced specifically in proximity to the news genre; they have taken on proportions that permeate different genres. As for linguistic resources, they are important in producing disinformation, but, by themselves, they are not enough to detect disinformation, which is why the importance of media education